AODV-PNT Performance Study with Added Factor Number of Neighbor Nodes on VANET - Grezio Arifiyan; Supeno Djanali; Radityo Anggoro (IPTEK Journal of Proceedings Series, 2018)
VANET (Vehucular Ad hoc Network) is a development of Mobile Ad hoc Network or often called MANET. The topology of VANET can change rapidly because of the movement of the node so that the topology can change dynamically, otherwise there is an interesting problem to be investigated on VANET ie connectivity between nodes. AODV protocol routing is further developed one of them is AODV-PNT, by adding prediction of node trend (Prediction Node Trend) by calculating TWR (Total Weight of The Route). In this study the factors - factors in determining TWR